Estrategias lúdicas para fomentar la práctica de valores en los estudiantes de tercer grado de la Escuela de Educación Básica Miguel Riofrío del cantón Loja en el periodo 2017-2018. - Japon Cabrera, Lizett Carolina (2018)
The research that deals with Playful Strategies to promote the practice of values in the third grade students of the Miguel Riofrío School of Basic Education of the Loja canton in the period 2017-2018., Whose general objective is to apply play strategies to encourage the practice of values in the third grade students of the School of EGB Miguel Riofrío of the Loja canton in the period 2017-2018. The population of the research was constituted by two teachers and 46 students of third grade "A" and "B" of the School of EGB "Miguel Riofrío"; the sample was of a non-probabilistic type, since it was worked with a teacher and 21 third grade students parallel "B" of EGB. The type of study was descriptive that frames a mixed (quantitative-qualitative) approach and a quasi-experimental design. The materials were: technological and desktop; the methods: scientific, observational, inductive-deductive, hermeneutic, descriptive, analytic-synthetic and statistical; techniques: participant observation, survey and interview and instruments: observation guide and questionnaire; the procedures: theoretical-diagnostic foundation, design, application and evaluation of the alternative proposal. As a result, the students present deficiencies and ignorance of the values, since the teacher did not use playful strategies to encourage the practice of values. It is concluded that the use of playful strategies to promote values if they are important allows us to develop fully and live in harmony with society.